Orai inhibition modulates pulmonary ILC2 metabolism and alleviates airway hyperreactivity in murine and humanized models - Emily Howard; Benjamin P. Hurrell; Doumet Georges Helou; Pedram Shafiei-Jahani; Spyridon Hasiakos; Jacob Painter; Sonal Srikanth; Yousang Gwack; Omid Akbari (Nature Communications, 2023)
Abstract Ca2+ entry via Ca2+ release-activated Ca2+ (CRAC) channels is a predominant mechanism of intracellular Ca2+ elevation in immune cells. Here we show the immunoregulatory role of CRAC channel components Orai1 and Orai2 in Group 2 innate lymphoid cells (ILC2s), that play crucial roles in the induction of type 2 inflammation. We find that blocking or genetic ablation of Orai1 and Orai2 downregulates ILC2 effector function and cytokine production, consequently ameliorating the development of ILC2-mediated airway inflammation in multiple murine models. Mechanistically, ILC2 metabolic and mitochondrial homeostasis are inhibited and lead to the upregulation of reactive oxygen species production. We confirm our findings in human ILC2s, as blocking Orai1 and Orai2 prevents the development of airway hyperreactivity in humanized mice. Our findings have a broad impact on the basic understanding of Ca2+ signaling in ILC2 biology, providing potential insights into the development of therapies for the treatment of allergic and atopic inflammatory diseases.